PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK (ITE) YANG MELANGGAR KESUSILAAN - Salma Intan Saraswati; Made Warka; Sri Setyadji (Jurnal Inovasi Penelitian, 2022)
In the era of globalization, progress in all fields is growing very rapidly, one of which is in the field of technology and information. Information technology is not only able to increase the progress of development, welfare, and civilization, but also can cause negative changes that are not in accordance with the existing legal rules. The development of science and technology has an impact on the development of law, including criminal law, especially criminal acts. Forms of criminal acts that occur in society are criminal acts that violate decency in the field of Information and Electronic Transactions. Most of the victims of crime are women. Like the case of Baiq Nuril Maknun who was supposed to be a victim but instead became a suspect. The problem of the Baiq Nuril Maknun case is phenomenal because it has received a lot of attention from the public, practitioners, academics and even the President. This case began with Baiq Nuril Maknun working as a temporary employee at SMAN 7 Mataram, who recorded a telephone conversation with the principal of the school, which was then reported by the principal to violate Article 27 paragraph (1) in conjunction with Article 45 paragraph (1) of the Electronic Information and Transaction Law.